A mobile app for police to track vehicle status - Bekkari ,Haithem; Drihem ,Abdelmoumen (Université of Eloued جامعة الوادي, 2026)
Our project aims to design and develop a mobile application dedicated to assisting police officers in efficiently tracking and managing vehicle status in real time. The goal is to create a reliable tool that simplifies the verification of vehicle information, facilitates the detection of violations, and supports more effective law enforcement interventions. The project began with a thorough analysis of existing vehicle tracking and law enforcement systems, identifying key challenges and areas for improvement. This groundwork helped us define the application's core features and user experience. UML diagrams were used to model the architecture and interactions within the system. We adopted Kotlin with Jetpack Compose for building a modern and intuitive user interface, and utilized a Node.js backend connected to a MySQL database to handle data management and communication. The application provides functionalities such as instant access to vehicle records, anomaly reporting, and the verification of administrative documents. The proposed solution empowers police officers with a streamlined and responsive tool, enhancing operational efficiency, ensuring quick access to critical data, and contributing to more organized and informed field operations.
Bachelor's thesis in Computer Science
Keywords: Mobile Application; Police; Vehicle Management; vehicle Status Tracker; Kotlin; Node.js; Express.